Induction of A Disintegrin and Metalloproteinase with Thrombospondin motifs 1 by a rare variant or cognitive activities reduces hippocampal amyloid-β and consequent Alzheimer’s disease risk - Qiu, Yunjie; Sha, Longze; Zhang, Xiuneng; Li, Guanjun; Zhu, Wanwan; Xu, Qi (Frontiers in Aging Neuroscience, 2022)
Amyloid-β (Aβ) derived from amyloid precursor protein (APP) hydrolysis is acknowledged as the predominant hallmark of Alzheimer's disease (AD) that especially correlates to genetics and daily activities. In 2019, meta-analysis of AD has discovered five new risk loci among which A Disintegrin and Metalloproteinase with Thrombospondin motifs 1 (ADAMTS1) has been further suggested in 2021 and 2022. To verify the association, we re-sequenced ADAMTS1 of clinical AD samples and subsequently identified a novel rare variant c.–2067A>C with watchable relevance (whereas the P-value was not significant after adjustment). Dual-luciferase assay showed that the variant sharply stimulated ADAMTS1 expression. In addition, ADAMTS1 was also clearly induced by pentylenetetrazol-ignited neuronal activity and enriched environment. Inspired by the above findings, we investigated ADAMTS1’s role in APP metabolism in vitro and in vivo. Results showed that ADAMTS1 participated in APP hydrolysis and consequently decreased Aβ generation through inhibiting β-secretase-mediated cleavage. In addition, we also verified that the hippocampal amyloid load of AD mouse model was alleviated by the introduction of ADAMTS1, and thus spatial cognition was restored as well. This study revealed the contribution of ADAMTS1 to the connection of genetic and acquired factors with APP metabolism, and its potential in reducing hippocampal amyloid and consequent risk of AD.